Coating composition, cured coating film, and method for producing the same

The coating composition, featuring urethane (meth)acrylate and specific particles, addresses the challenges of maintaining low gloss and effective resistance to scratches and dirt by forming a cured film with enhanced coating properties and a texture similar to unpainted wood.

JP2025048711APending Publication Date: 2025-04-03CHUGOKU MARINE PAINTS

Patent Information

Application Number
JP2024060415
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-21
Filing Date
2024-04-03
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

Existing low-gloss painted wood products struggle with noticeable gloss changes due to scratches and scuffs, and are prone to dirt accumulation, making it difficult to achieve both the texture of unpainted wood and effective coating properties like pollution resistance, chemical resistance, and rubbing resistance.

Method used

A coating composition comprising urethane (meth)acrylate, (meth)acrylate monomer, a photoinitiator, and particles with specific weight average molecular weight and average particle size, which forms a cured coating film with excellent coating properties and a low gloss texture similar to unpainted wood.

Benefits of technology

The coating composition effectively forms a cured coating film with superior pollution resistance, chemical resistance, and rubbing resistance while maintaining a low gloss finish that mimics the texture of unpainted wood.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025048711000001
    Figure 2025048711000001
  • Figure 2025048711000002
    Figure 2025048711000002
  • Figure 2025048711000003
    Figure 2025048711000003
Patent Text Reader

Abstract

To provide a coating composition that enables the formation of a cured coating film exhibiting excellent film properties such as stain resistance, chemical resistance, and gloss durability against abrasion, while reproducing the natural texture of uncoated wood through low gloss.SOLUTION: A coating composition according to the present invention comprises a urethane (meth)acrylate (A), a (meth)acrylate monomer (B), a photopolymerization initiator (C), and particles (D), wherein the weight-average molecular weight per functional group (Mw / F) of the urethane (meth)acrylate (A) is 1,500 or more, and the average particle diameter (D50) of the particles (D) is 5.0 μm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating composition. The present invention also relates to a cured coating film formed from the coating composition and a method for producing the same. [Background technology]

[0002] Traditionally, natural wood has been used in wooden building materials, and is widely used in interior design because it gives a room a natural warmth and calmness compared to artificial materials. In recent years, there has been a demand for natural finishes that make better use of the natural texture of wood for wooden building materials, and there has been a trend toward high demand for painted products with low gloss finishes, such as unpainted wood. Note that "unpainted wood" refers to wood that has been processed and has been ground down with abrasive paper or the like, and has the texture of unpainted wood.

[0003] There are similar low-gloss building materials that are made by laminating decorative sheets printed with a grain pattern, but compared to unpainted wood, the texture is visually different in terms of gloss and the misalignment of the grain and embossing (unevenness). In addition, to express the texture of unpainted wood with wooden building materials, it is necessary to obtain an equivalent texture when viewed from various angles. For example, it is known that the 60° gloss level, which is used as a general gloss evaluation, can be adjusted to a specific value or lower, and a similar texture can be obtained by finishing to an equivalent value or lower for 85° gloss levels in addition to 60° gloss levels.

[0004] For example, Patent Document 1 proposes a decorative sheet that has low gloss due to a matte effect and excellent appearance, which includes a substrate and a surface layer, the surface layer being a continuous layer composed of an ultraviolet light cured material layer and an excimer light cured material layer, the continuous layer being composed of a dispersion of at least one of organic particles and inorganic particles, and the surface roughness Sa of the surface layer being adjusted to be within a specific range. Patent Document 2 proposes a matte article having an excellent matte effect in visibility and texture, and also having a smooth feel, in which at least a part of the surface has a surface shape in which Ssk (skewness) is 0.00 or more and Sku (kurtosis) is 3.50 or less, as defined in ISO25178-2:2012, and which is provided with a matte layer, and the surface shape is formed by the surface of the matte layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2022-181354 [Patent Document 2] JP 2022-61031 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, while low-gloss painted products such as those described in Patent Documents 1 and 2 can obtain the texture of unpainted wood, compared to high-gloss painted products, changes in gloss due to scratches and rubbing are more noticeable and they tend to be more susceptible to dirt. There was a problem in that it was difficult to achieve both the texture of unpainted wood and the coating film properties such as resistance to contamination, chemical resistance, and abrasion resistance.

[0007] Therefore, an object of the present invention is to provide a coating composition capable of forming a cured coating film that has excellent coating film physical properties such as stain resistance, chemical resistance, and abrasion resistance while realizing the texture of unpainted wood due to its low gloss. [Means for solving the problem]

[0008] As a result of intensive research, the present inventors have found that a coating composition contains a urethane (meth)acrylate (A) having a specific weight average molecular weight, a (meth)acrylate monomer (B), a photopolymerization initiator (C), and a specific average particle diameter (D 50It has been found that the above problems can be solved by incorporating particles (D) having the above-mentioned structure. The present invention has been completed based on this finding.

[0009] That is, according to the present invention, the following inventions are provided. [1] A coating composition comprising a urethane (meth)acrylate (A), a (meth)acrylate monomer (B), a photopolymerization initiator (C) and particles (D), The weight average molecular weight (Mw / F) per functional group of the urethane (meth)acrylate (A) is 1,500 or more, The average particle diameter (D 50 ) is 5.0 μm or more. [2] The coating composition according to [1], wherein the number of functional groups of the urethane (meth)acrylate (A) is 3 or more. [3] The coating composition according to [1] or [2], wherein the particles (D) include organic particles. [4] The coating composition according to [3], wherein the organic particles are urethane resin particles. [5] The average particle diameter (D 50 ) is 8.0 μm or more. [6] The coating composition according to any one of [1] to [5], wherein the content of the particles (D) is 5.0 mass% or more relative to 100 mass% of the solid content of the coating composition. [7] The coating composition according to any one of [1] to [6], which is for excimer UV curing. [8] A cured coating film formed from a coating composition containing a urethane (meth)acrylate (A), a (meth)acrylate monomer (B), a photopolymerization initiator (C) and particles (D), the developed area ratio Sdr of the interface on one surface of the cured coating film is 0.300 or more, and the arithmetic mean curve Spc of the peaks is 3,000 or more; The particles (D) in the cured coating film have an average particle size of 3.2 μm or more. [9] A step of applying a coating composition containing a urethane (meth)acrylate (A), a (meth)acrylate monomer (B), a photopolymerization initiator (C) and particles (D) onto a substrate; a step of irradiating the coated surface of the substrate with excimer UV light to form a cured coating film having an interface developed area ratio Sdr of 0.300 or more, an arithmetic mean curve Spc of the peaks of 3,000 or more, and an average particle size of the particles (D) in the cured coating film of 3.2 μm or more; A method for producing a cured coating film comprising the steps of: Effect of the Invention

[0010] According to the present invention, it is possible to provide a coating composition capable of forming a cured coating film that realizes the texture of uncoated wood due to its low gloss and is excellent in coating film physical properties such as stain resistance, chemical resistance, and abrasion resistance. Also, according to the present invention, it is possible to provide a cured coating film that is excellent in stain resistance, chemical resistance, and abrasion resistance, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will now be described in more detail. In this specification, "(meth)acrylate" refers to acrylate and methacrylate, and "(meth)acryloyl" refers to acryloyl and methacryloyl. Furthermore, the "solid content" refers to the coating composition excluding volatile components such as organic solvents.

[0012] <Paint composition> The coating composition according to the present invention contains at least a urethane (meth)acrylate (A), a (meth)acrylate monomer (B), a photopolymerization initiator (C) and particles (D). Such a coating composition can form fine wrinkles on the coating surface by ultra-short wavelength UV curing (excimer UV curing) using an excimer lamp, forming a low gloss coating film. Such a coating composition can form a cured coating film that has excellent coating film physical properties such as stain resistance, chemical resistance, and abrasion resistance while realizing the texture of uncoated wood due to its low gloss.

[0013] The average particle diameter (D 20 , D 50 , D 70 ) is D 20 is preferably 4.5 μm or more and 20.0 μm or less, more preferably 6.5 μm or more and 15.5 μm or less, and D 50 is 5.0 μm or more, preferably 6.0 μm or more and 25.0 μm or less, more preferably 8.0 μm or more and 23.0 μm or less, and further preferably 9.5 μm or more and 22.0 μm or less, and D 70 is preferably 7.0 μm or more and 30.0 μm or less, and more preferably 10.0 μm or more and 27.5 μm or less. 20 , D 50 , D 70 When the value of Sdr is within the above range, fine wrinkles are formed on the coating surface, making it easier to obtain the desired surface shape (developed area ratio Sdr of the surface interface, arithmetic mean curve Spc of the peaks). The average particle diameter (D 20 , D 50 , D 70 ) is a value measured by a laser diffraction / scattering method, and can be measured, for example, using a laser diffraction / scattering type particle size distribution measuring device "Microtrac MT3000II" (manufactured by Microtrac Bell).

[0014] Each component of the coating composition according to the present invention will now be described in detail.

[0015] (Urethane (meth)acrylate (A)) Urethane (meth)acrylate (A) has an acryloyl group (CH 2 =CHCO-) ​​and / or methacryloyl groups (CH 2 =C(CH 3)CO-) and a urethane bond (-NH·COO-). The urethane (meth)acrylate is not particularly limited, but can be obtained, for example, by reacting a polyisocyanate with a hydroxyl group-containing (meth)acrylate and, if necessary, with a polyol other than the hydroxyl group-containing (meth)acrylate. The urethane (meth)acrylate (A) is preferably an oligomer or polymer, and more preferably an oligomer.

[0016] The polyisocyanate is obtained by reacting a polyol with a diisocyanate. The polyol, which is a raw material for synthesizing the polyisocyanate, is not particularly limited, but examples thereof include polyester polyol, polyether polyol, polycarbonate polyol, etc., and only one of these may be used, or two or more of them may be used in combination.

[0017] There are no particular limitations on the production method of the polyester polyol, and it is possible to use polyester polyols obtained by known methods, such as by polycondensation reaction of a diol with a dicarboxylic acid or a dicarboxylic acid chloride, or by esterification of a diol or a dicarboxylic acid and then subjecting it to an ester exchange reaction. The diol used in the synthesis of the polyester polyol is not particularly limited, but examples thereof include ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, tetraethylene glycol, and tetrapropylene glycol. The dicarboxylic acid used in the synthesis of the polyester polyol is not particularly limited, but examples thereof include adipic acid, succinic acid, glutaric acid, pimelic acid, sebacic acid, azelaic acid, dimaleic acid, terephthalic acid, isophthalic acid, and phthalic acid.

[0018] The polyether polyol is not particularly limited, but examples thereof include polyethylene oxide, polypropylene oxide, and ethylene oxide-propylene oxide random copolymers.

[0019] The polycarbonate polyol is not particularly limited, but examples thereof include reaction products obtained by polycondensation of the following components A and B. That is, the component A is not particularly limited, but examples thereof include diols such as 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, 1,8-octanediol, 1,9-nonanediol, 1,4-cyclohexanedimethanol, 2-methylpropanediol, dipropylene glycol, and diethylene glycol, and reaction products of these diols with dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, adipic acid, azelaic acid, and hexahydrophthalic acid. Component B is not particularly limited, but examples thereof include aromatic carbonates or aliphatic carbonates such as diphenyl carbonate, bis(chlorophenyl) carbonate, dinaphthyl carbonate, phenyltoluyl carbonate, phenylchlorophenyl carbonate, 2-tolyl-4-tolyl carbonate, dimethyl carbonate, diethyl carbonate, diethylene carbonate, and ethylene carbonate.

[0020] The diisocyanate which is a raw material for synthesizing polyisocyanate is not particularly limited, but may be a straight-chain or alicyclic aliphatic diisocyanate, or an aromatic diisocyanate. Specific examples of the diisocyanate include linear hydrocarbon group-containing diisocyanates such as tetramethylene diisocyanate and hexamethylene diisocyanate; branched hydrocarbon group-containing diisocyanates such as 2,2,4-trimethylhexamethylene diisocyanate; cyclic hydrocarbon group-containing diisocyanates such as isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylene diisocyanate and hydrogenated toluene diisocyanate; and aromatic hydrocarbon group-containing diisocyanates such as p-phenylene diisocyanate, 3,3'-dimethyldiphenyl-4,4'-diisocyanate, 1,3-xylene diisocyanate, dianisidine diisocyanate, tetramethylxylene diisocyanate, 1,5-naphthalene diisocyanate, tolylene diisocyanate and 4,4-diphenylmethane diisocyanate.

[0021] As the hydroxyl group-containing (meth)acrylate, a (meth)acrylate having at least one hydroxyl group, preferably 1 to 5 hydroxyl groups, can be used. In addition, such a hydroxyl group-containing (meth)acrylate preferably has a hydrocarbon moiety having 2 to 20 carbon atoms. Here, the hydrocarbon moiety refers to an organic group having a linear or branched aliphatic hydrocarbon group, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group, and the aliphatic hydrocarbon group and the alicyclic hydrocarbon group may be saturated or unsaturated. In addition, a part of the hydrocarbon moiety may contain an ether bond (COC bond).

[0022] Examples of the (meth)acrylate monomer having a hydroxyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate, and their caprolactone adducts (e.g., Plaxel FA1 and FA2 manufactured by Daicel Corporation); hydroxyl-terminated polyalkylene glycol mono(meth)acrylates such as polyethylene glycol mono(meth)acrylate and polypropylene glycol mono(meth)acrylate; ethylene oxide modified products thereof (e.g., AM-90G and AM-130G manufactured by Shin-Nakamura Chemical Co., Ltd.; Light Acrylate EC-A, MTG-A, and EHDG-AT manufactured by Kyoeisha Chemical Co., Ltd.); glycerin mono(meth)acrylate (e.g., Blenmer GLM manufactured by NOF Corporation); and glycerin diacrylate. Examples of such compounds include (meth)acrylates (such as Aronix MT3560 manufactured by Toagosei Co., Ltd.), isocyanuric acid EO-modified di(meth)acrylates (such as Aronix M-313 and 315 manufactured by Toagosei Co., Ltd.), pentaerythritol tri(meth)acrylates (such as Viscoat 300 manufactured by Osaka Organic Chemical Industry Co., Ltd., Aronix M-305, M-306, and MT-3548 manufactured by Toagosei Co., Ltd., Light Acrylate PE-3A manufactured by Kyoeisha Chemical Co., Ltd., and NK Ester A-TMM-3L manufactured by Shin-Nakamura Chemical Co., Ltd.), and dipentaerythritol penta(meth)acrylates (such as Aronix M-400, M-402, M-403, and MT-3549 manufactured by Toagosei Co., Ltd., Light Acrylate DPE-6A manufactured by Kyoeisha Chemical Co., Ltd., and NK Ester A-DPH manufactured by Shin-Nakamura Chemical Co., Ltd.). Such hydroxyl group-containing (meth)acrylates may be used alone or in combination of two or more.

[0023] As the polyol other than the hydroxyl group-containing (meth)acrylate, which is used as necessary, known polyols such as polyether polyols, polyester polyols, polyolefin polyols, etc. can be used. Specific examples include polyoxyethylene glycol, polyoxypropylene glycol, polyoxytetramethylene glycol, ethylene oxide adduct of bisphenol A, propylene oxide adduct of bisphenol A, polycaprolactone polyols, alkylene diols, etc. Such polyols may be used alone or in combination of two or more.

[0024] Among the above urethane (meth)acrylates, polyfunctional urethane (meth)acrylates are preferred. The number of functional groups in the urethane (meth)acrylate is preferably 2 or more, more preferably 3 or more, and may be 12 or less, or may be 10 or less.

[0025] The weight average molecular weight (Mw / F) per functional group of the urethane (meth)acrylate is preferably 1,500 or more, more preferably 1,500 to 10,000, and even more preferably 1,500 to 6,000. If the weight average molecular weight (Mw / F) per functional group of the urethane (meth)acrylate is within the above range, it can form a cured coating film that has excellent coating film physical properties such as stain resistance, chemical resistance, and abrasion resistance while achieving the texture of unpainted wood due to its low gloss. The weight average molecular weight (Mw, Mw mix The weight average molecular weight (Mw, Mw) and number average molecular weight (Mn) of the urethane (meth)acrylate oligomer can be measured using gel permeation chromatography (GPC). mix ) and number average molecular weight (Mn) are values ​​calculated in terms of standard polystyrene. When one type of urethane (meth)acrylate oligomer is used, the weight average molecular weight (Mw / F) per functional group of a single urethane (meth)acrylate oligomer is calculated as follows. Weight average molecular weight per functional group of urethane (meth)acrylate oligomer (Mw / F) = Weight average molecular weight of urethane (meth)acrylate oligomer (Mw) / Number of functional groups of urethane (meth)acrylate oligomer (F) When multiple types of urethane (meth)acrylate oligomers are used, the weight average molecular weight (Mw mix / F mix The calculation method for is as follows: When n types of urethane (meth)acrylate oligomers are mixed, the mixed urethane (meth)acrylate oligomers are assumed to be one urethane (meth)acrylate oligomer, and the number of functional groups is calculated using the following formula. Number of functional groups of mixed urethane (meth)acrylate oligomer (F mix )={(mass (g) of urethane (meth)acrylate oligomer 1 / number average molecular weight Mn of urethane (meth)acrylate oligomer 1×number of functional groups of urethane (meth)acrylate oligomer 1)+(mass (g) of urethane (meth)acrylate oligomer 2 / number average molecular weight Mn of urethane (meth)acrylate oligomer 2×number of functional groups of urethane (meth)acrylate oligomer 2) +··· + (mass (g) of urethane (meth)acrylate oligomer n / number average molecular weight Mn of urethane (meth)acrylate oligomer n × number of functional groups of urethane (meth)acrylate oligomer n)} / {(mass (g) of urethane (meth)acrylate oligomer 1 / number average molecular weight Mn of urethane (meth)acrylate oligomer 1) + (mass (g) of urethane (meth)acrylate oligomer 2 / number average molecular weight Mn of urethane (meth)acrylate oligomer 2) +··· + (mass (g) of urethane (meth)acrylate oligomer n / number average molecular weight Mn of urethane (meth)acrylate oligomer n)} The weight average molecular weight (Mw) per functional group of a urethane (meth)acrylate oligomer that is a mixture of multiple types of urethane (meth)acrylate oligomers. mix / Fmix ) = Weight average molecular weight (Mw) of a urethane (meth)acrylate oligomer obtained by mixing multiple types of urethane (meth)acrylate oligomers mix ) / Functional group number of mixed urethane (meth)acrylate oligomer (F mix )

[0026] From the viewpoint of coating film properties, the content of the urethane (meth)acrylate is preferably from 10 to 70% by mass, more preferably from 20 to 60% by mass, and even more preferably from 25 to 50% by mass, relative to 100% by mass of the solid content of the coating composition.

[0027] ((Meth)acrylate Monomer (B)) The (meth)acrylate monomer (B) is a monomer having at least one (meth)acryloyl group (excluding component (A)). The (meth)acrylate monomer forms a cured coating film together with the urethane (meth)acrylate when the coating composition is irradiated with ultraviolet light. The (meth)acrylate monomer may also function as a reactive diluent that adjusts the viscosity of the coating composition.

[0028] The number of functional groups of the (meth)acrylate monomer is not particularly limited, but is preferably 1 or more and 6 or less, and more preferably 1 or 2.

[0029] Examples of the monofunctional and difunctional (meth)acrylate monomers include (meth)acryloylmorpholine, phenoxy polyethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxytetraethylene glycol (meth)acrylate, ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and the like. alkylene glycol di(meth)acrylates such as acrylate, 1,10-decanediol diacrylate, and neopentyl glycol di(meth)acrylate; diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and polytetramethylene glycol di(meth)acrylate. di(meth)acrylates of halogen-substituted alkylene glycols such as tetrafluoroethylene glycol di(meth)acrylate; di(meth)acrylates of aliphatic polyols such as trimethylolpropane di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, and pentaerythritol di(meth)acrylate; hydrogenated dicyclopentadienyl di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, and other hydrogenated dicyclopentadienyl di(meth)acrylates. Di(meth)acrylates of dioxane glycol or dioxane dialkanol, such as 1,3-dioxane-2,5-diyl di(meth)acrylate (also known as dioxane glycol di(meth)acrylate); di(meth)acrylates of alkylene oxide adducts of bisphenol A or bisphenol F, such as ethylene oxide adduct diacrylate of bisphenol A and ethylene oxide adduct diacrylate of bisphenol F;Examples of the epoxy di(meth)acrylate of bisphenol A or bisphenol F, such as an acrylic acid adduct of bisphenol A diglycidyl ether or an acrylic acid adduct of bisphenol F diglycidyl ether; silicone di(meth)acrylate; di(meth)acrylate of hydroxypivalic acid neopentyl glycol ester; 2,2-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane; 2,2-bis[4-(meth)acryloyloxyethoxyethoxycyclohexyl]propane; di(meth)acrylate of 2-(2-hydroxy-1,1-dimethylethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane; tris(hydroxyethyl)isocyanurate di(meth)acrylate; and the like. Among these bifunctional (meth)acrylate monomers, alkylene glycol di(meth)acrylate, polyoxyalkylene glycol di(meth)acrylate, di(meth)acrylate of halogen-substituted alkylene glycol, di(meth)acrylate of aliphatic polyol, di(meth)acrylate of hydrogenated dicyclopentadiene or tricyclodecane dialkanol, di(meth)acrylate of dioxane glycol or dioxane dialkanol, silicone di(meth)acrylate, Examples of the di(meth)acrylate include di(meth)acrylate of hydroxypivalic acid neopentyl glycol ester, 2,2-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane, 2,2-bis[4-(meth)acryloyloxyethoxyethoxycyclohexyl]propane, di(meth)acrylate of 2-(2-hydroxy-1,1-dimethylethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane, and tris(hydroxyethyl)isocyanurate di(meth)acrylate. These (meth)acrylate monomers may be modified monomers such as silicone modified and fluorine modified. These (meth)acrylate monomers may be used alone or in combination of two or more.;

[0030] Examples of the trifunctional to hexafunctional (meth)acrylate monomers include glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, EO-added trimethylolpropane tri(meth)acrylate, PO-added trimethylolpropane tri(meth)acrylate (PO portion is n=2), PO-added trimethylolpropane tri(meth)acrylate (PO portion is n=3), glycerin PO-added tri(meth)acrylate, 2-(meth)acryloyloxypropyl tetrahydrohydrogen terephthalate, PO-added glycol tri(meth)acrylate, tris(meth)acryloyloxyethyl fluoride, and the like. Examples of the monomer include phosphate, pentaerythritol tri(meth)acrylate, EO-added pentaerythritol tri(meth)acrylate, tris((meth)acryloxyethyl)isocyanurate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, alkoxylated dipentaerythritol hexa(meth)acrylate, EO-added pentaerythritol tetra(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, polycaprolactone-modified dipentaerythritol hexa(meth)acrylate, and alkylene oxide-modified dipentaerythritol polyfunctional (meth)acrylate. These (meth)acrylate monomers may be modified monomers by silicone modification, fluorine modification, or the like. These (meth)acrylate monomers can be used alone or in combination of two or more.

[0031] From the viewpoint of coating film properties, the content of the (meth)acrylate monomer is preferably 20% by mass or more and 80% by mass or less, more preferably 30% by mass or more and 70% by mass or less, and even more preferably 40% by mass or more and 60% by mass or less, relative to 100% by mass of the solid content of the coating composition.

[0032] (Photopolymerization initiator (C)) The photopolymerization initiator (C) is not particularly limited, and a conventionally known photopolymerization initiator for UV curing can be used. Examples of the photopolymerization initiator include acylphosphine oxide-based photopolymerization initiators, acetophenone-based photopolymerization initiators, benzoyl formate-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, oxime ester-based photopolymerization initiators, hydroxybenzoyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, and α-aminoalkylphenone-based photopolymerization initiators.

[0033] Examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoylphenylethoxyphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the acetophenone-based photopolymerization initiator include acetophenone, 3-methylacetophenone, benzyl dimethyl ketal, 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one. Benzoyl formate-based photopolymerization initiators include methyl benzoyl formate and the like. An example of the thioxanthone-based photopolymerization initiator is isopropylthioxanthone. Examples of the oxime ester photopolymerization initiator include 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime), and the like. Examples of the hydroxybenzoyl-based photopolymerization initiator include benzoin alkyl ethers. Benzophenone-based photopolymerization initiators include benzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, 4-chlorobenzophenone, and 4,4'-diaminobenzophenone. Examples of the α-aminoalkylphenone photopolymerization initiator include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, and the like. These photopolymerization initiators may be used alone or in combination of two or more.

[0034] From the viewpoint of the curability and transparency of the cured coating film, the content of the photopolymerization initiator is preferably 0.1 mass % or more and 10.0 mass % or less, more preferably 1.0 mass % or more and 7.0 mass % or less, and even more preferably 2.0 mass % or more and 5.0 mass % or less, relative to 100 mass % of the solid content of the coating composition.

[0035] (Particle (D)) The particles (D) are not particularly limited, and conventionally known organic particles and inorganic particles for coating compositions can be used, with the use of organic particles being preferred. Examples of organic particles include resin particles such as urethane resin, (meth)acrylic resin, polyamide resin, silicone rubber, melamine resin, polycarbonate, polystyrene, polyvinyl chloride resin, benzoguanamine-melamine-formaldehyde condensate, fluorine resin, and polyester resin. Among these, urethane resin particles are preferred. Examples of inorganic particles include inorganic particles of silica, glass, mica, zeolite, diatomaceous earth, graphite, potassium feldspar, kaolin, clay, talc, calcium carbonate, barium sulfate, magnesium carbonate, alumina, and aluminosilicate. These particles may be used alone or in combination of two or more kinds.

[0036] The average particle size (D 50 ) is preferably 5.0 μm or more, more preferably 9.5 μm or more, and is preferably 30 μm or less, more preferably 25 μm or less. 50 ) within the above range, a cured coating film can be formed that has excellent coating film physical properties such as stain resistance, chemical resistance, and abrasion resistance while realizing the texture of unpainted wood due to its low gloss. The average particle diameter (D 50 ) is a value measured by a laser diffraction / scattering method, and can be measured, for example, using a laser diffraction / scattering type particle size distribution measuring device "Microtrac MT3000II" (manufactured by Microtrac Bell).

[0037] From the viewpoint of coating film properties, the particle content is preferably 5.0% by mass or more, and more preferably 5.0% by mass or more and 30% by mass or less, relative to 100% by mass of the solid content of the coating composition.

[0038] (Other Ingredients) In addition to the above-mentioned components, the coating composition according to the present invention may further contain, as necessary, polymerization inhibitors, organic solvents (non-reactive diluents), defoamers, anti-settling agents, leveling agents, dispersants, heat stabilizers, ultraviolet absorbers, light stabilizers, anti-fouling agents, substrate adhesion improvers, photosensitizers, antistatic agents, scratch resistance agents, anti-fungal agents, antibacterial agents, anti-viral agents, silane coupling agents, plasticizers, etc., within the scope of the invention.

[0039] The coating composition according to the present invention may be either a solvent-based coating composition that is diluted with an organic solvent (non-reactive diluent), or a solventless coating composition that does not need to be diluted with an organic solvent. However, a solventless coating composition is preferable because it leaves no residual volatile organic compounds (VOCs), has no effect on the human body, and is environmentally friendly. In addition, the solventless coating composition does not require a drying process, so that the production efficiency in industrial use can be improved.

[0040] (Method of preparing coating composition) The coating composition according to the present invention can be obtained by mixing and stirring the above-mentioned components using a conventionally known device such as a mixer, disperser, stirrer, etc. Examples of such devices include a disperser, a mixing / dispersing mill, a mortar mixer, a roll, a paint shaker, a homogenizer, etc.

[0041] [Cured coating film] The cured coating film according to the present invention is formed from a coating composition containing a urethane (meth)acrylate (A), a (meth)acrylate monomer (B), a photopolymerization initiator (C) and particles (D). Components (A) to (D) are as described above.

[0042] The cured coating film has a developed area ratio Sdr of the interface on one surface of 0.300 or more, preferably 0.300 or more and 1.000 or less, and more preferably 0.3000 or more and 0.800 or less. Furthermore, the cured coating film has an arithmetic mean curve Spc of the peaks on one surface of 3,000 or more, preferably 3,000 or more and 5,000 or less, and more preferably 3,000 or more and 4,500 or less. When the interfacial developed area ratio Sdr of one surface of the cured coating film and the arithmetic mean curve Spc of the peaks are within the above numerical ranges, the cured coating film formed on the wood substrate has a low gloss and can achieve the texture of unpainted wood. The developed area ratio Sdr and the arithmetic mean curve Spc of the peaks of the cured coating film are values ​​measured in accordance with ISO25178, and can be measured using a shape analysis laser microscope ("VK-X1000 (controller unit) / VK-X1050 (measurement unit)", manufactured by Keyence Corporation).

[0043] The average particle size of the particles (D) in the cured coating film is 3.2 μm or more, preferably 4.0 μm or more and 25.0 μm or less, more preferably 5.0 μm or more and 20.0 μm or less, and even more preferably 6.0 μm or more and 15.0 μm or less. The average particle diameter of the particles (D) in the cured coating film is measured by using an energy dispersive X-ray analyzer (EDX) attached scanning electron microscope (SEM), such as "S-3400N" (manufactured by Hitachi High-Tech Corporation) or a shape analysis laser microscope, such as "VK-X1000 (controller unit) / VK-X1050 (measurement unit)" (manufactured by Keyence Corporation), and the longest diameter of the particles is taken as the particle diameter, regardless of the shape of the particles (D), and 40 random particles are measured and the average value of these particle diameters is taken as the average value. The above-mentioned devices (energy dispersive X-ray analyzer (EDX) attached scanning electron microscope (SEM) and shape analysis laser microscope) can be appropriately selected and used depending on the shape (regular, irregular) and components (inorganic, organic) of the particles (D). In a preferred embodiment of the present invention, when the particles (D) are inorganic particles, the average particle size is preferably determined using an energy dispersive X-ray analyzer (EDX) with a scanning electron microscope (SEM), and when the particles (D) are organic particles, the average particle size is preferably determined using a shape analysis laser microscope. When both inorganic and organic particles are contained in the cured coating film, the average value of the measurement results obtained by both measurement methods of the above-mentioned devices is regarded as the average particle size.

[0044] The thickness of the cured coating film is not particularly limited, but from the viewpoints of drying property, curing property, coating film properties, etc., it is preferably 5 μm to 30 μm, more preferably 8 μm to 20 μm, and even more preferably 10 μm to 15 μm. The film thickness in the present invention refers to the thickness of the cured coating film when the cross section of the cured coating film is observed with an optical microscope, a scanning electron microscope (SEM), or the like. When forming a coating film with such a thickness, a coating film of the desired thickness may be formed by one coating, or a coating film of the desired thickness may be formed by multiple coatings.

[0045] [Method of manufacturing cured coating film] The method for producing a cured coating film according to the present invention includes a step of applying a coating composition onto a substrate (application step) and a step of forming a cured coating film (curing step).

[0046] (coating process) The coating composition to be applied on the substrate in the coating step is as described above. The coating method of the coating composition is not particularly limited, and a conventionally known coating method can be selected. For example, a coating machine such as a bar coater, a gravure coater, a roll coater (such as a natural roll coater and a reverse roll coater), a curtain flow coater, an air knife coater, a spin coater, and a blade coater can be used for the coating method. Among these, the coating method using a roll coater is preferred from the viewpoint of workability and productivity.

[0047] (base material) Examples of the substrate include wooden flooring, wall materials, ceiling materials, plywood, solid wood, hardboard, particle board, etc. The thickness of the wooden substrate is not particularly limited, but is usually about 1 to 50 mm.

[0048] (hardening process) In the curing step, the coating surface of the substrate is subjected to ultra-short wavelength UV curing (excimer UV curing) using an excimer lamp to cure the coating composition and form the above-mentioned cured coating film. The irradiation dose of the excimer UV is preferably 10 mJ / cm from the viewpoint of the curability of the coating composition. 2 More preferably, 25 mJ / cm2 More preferably, 35 mJ / cm 2 That's all. There is no particular upper limit, but taking into consideration productivity such as improved production efficiency, it is preferably 1,000 mJ / cm 2 Less than or equal to 500 mJ / cm 2 Less than 300 mJ / cm, more preferably 300 mJ / cm 2 The following is the result. In addition, the oxygen concentration during irradiation with light of the above wavelengths is preferably as low as possible, preferably 1,500 ppm or less, and more preferably 1,000 ppm or less. By curing the coating composition with excimer UV, fine wrinkles are formed on the coating surface, forming a low-gloss coating film that satisfies the above-mentioned surface shape (developed area ratio Sdr of the cured coating film and arithmetic mean curve Spc of the peaks).

[0049] In the curing step, in addition to excimer UV irradiation, the coating composition may be cured by UV curing using a conventional high-pressure mercury lamp (mercury lamp UV curing). The amount of irradiation by the mercury lamp UV is preferably 50 mJ / cm from the viewpoint of the curability of the coating composition. 2 More preferably, 100 mJ / cm 2 More preferably, 200 mJ / cm 2 The upper limit is not particularly limited, and in consideration of productivity such as improved production efficiency, it is preferably 1,000 mJ / cm 2 or less, more preferably 500 mJ / cm 2 or less, and more preferably 400 mJ / cm 2 The following is the result. EXAMPLES

[0050] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0051] First, in order to prepare the coating composition, the following raw materials were prepared. Component (A) Urethane (meth)acrylate 1: Functional group number 2, Mw 5,300, manufactured by MIWON SPECIALTY CHEMICAL Co., Ltd., Product name: MIRAMER SC2565 Urethane (meth)acrylate 2: Functional group number 3, Mw 5,400, synthetic product Urethane (meth)acrylate 3: Functional group number 3, Mw 1,800, manufactured by Negami Chemical Industries, Ltd., product name: ART RESIN SMT-001 Urethane (meth)acrylate 4: Functional group number 4, Mw 22,700, manufactured by Negami Chemical Industries, Ltd., product name: ART RESIN CWD-8E26 Urethane (meth)acrylate 5: Functional group number 4, Mw 1,500, manufactured by Daicel Allnex Co., Ltd., product name: EBECRYL 4666 Urethane (meth)acrylate 6: Functional group number 6, Mw 1,300, manufactured by Negami Chemical Industrial Co., Ltd., product name: ART RESIN UN-CMP-1 Urethane (meth)acrylate 7: Functional group number 10, Mw 19,500, synthetic product

[0052] (Synthesis of urethane (meth)acrylate 2) The above urethane (meth)acrylate 2 was synthesized by the following method. First, 450 parts by mass of polyester polyol (manufactured by Kuraray Co., Ltd., product name: Kuraray Polyol P-1012), 130 parts by mass of hydroxypropyl acrylate (manufactured by Osaka Organic Chemical Industry Ltd., product name: HPA), 84 parts by mass of pentaerythritol triacrylate (manufactured by Eternal, product name: PETRA), 231 parts by mass of tripropylene glycol diacrylate (manufactured by Osaka Organic Chemical Industry Ltd., product name: Viscoat 310HP), 0.04 parts by mass of 4-methoxyphenol, 0.04 parts by mass of dibutylhydroxytoluene, and 0.12 parts by mass of dibutyltin laurate were mixed and heated to 70°C. Subsequently, 262 parts by mass of hydrogenated MDI (manufactured by Covestro, product name: Desmodur W) was added dropwise over one hour at 70° C. After completion of the addition, the temperature was raised to 80° C. and maintained for four hours to obtain urethane (meth)acrylate 2 having 3 functional groups and a weight average molecular weight (Mw) of 5,400.

[0053] (Synthesis of urethane (meth)acrylate 7) The above urethane (meth)acrylate 7 was synthesized by the following method. First, 900 parts by mass of polyester polyol (manufactured by Kuraray Co., Ltd., product name: Kuraray Polyol P-2012), 400 parts by mass of pentaerythritol hexaacrylate (manufactured by Toagosei Co., Ltd., product name: Aronix M402), 669 parts by mass of tripropylene glycol diacrylate (manufactured by Osaka Organic Chemical Industry Ltd., product name: Viscoat 310HP), 0.12 parts by mass of 4-methoxyphenol, 0.12 parts by mass of dibutylhydroxytoluene, and 0.24 parts by mass of dibutyltin laurate were mixed and heated to 70°C. Subsequently, 262 parts by mass of hydrogenated MDI (manufactured by Covestro, product name: Desmodur W) was added dropwise over 1 hour at 70° C. After completion of the addition, the temperature was raised to 80° C. and maintained for 4 hours to obtain urethane (meth)acrylate 7 having 10 functional groups and a weight average molecular weight (Mw) of 19,500.

[0054] (B) Component (Meth)acrylate monomer 1: functional group number 1, acryloylmorpholine, manufactured by KJ Chemicals Co., Ltd., product name: ACMO (Meth)acrylate monomer 2: Functional group number 2, tripropylene glycol diacrylate, manufactured by MIWON SPECIALTY CHEMICAL, product name: TPGDA (Meth)acrylate monomer 3: Functional group number 2, 1,9-nonanediol diacrylate, manufactured by Kyoeisha Chemical Co., Ltd., product name: Light Acrylate 19ND-A (Meth)acrylate monomer 4: functional group number 2, 1-6-hexanediol diacrylate (EO) adduct, manufactured by MIWON SPECIALTY CHEMICAL Co., Ltd., product name: MIRAMER M202 (Meth)acrylate monomer 5: tricyclodecane dimethanol diacrylate with 2 functional groups, manufactured by Daicel Allnex Corporation, product name: EBECRYL 130

[0055] (C) Component Photopolymerization initiator 1: Methyl benzoyl formate, manufactured by ChemFine International, trade name: Hycure 55 Photopolymerization initiator 2: 2,4,6-trimethylbenzoyldiphenylphosphine oxide, manufactured by Chitec Technology Co., Ltd., product name: CHIVACURE TPO Photopolymerization initiator 3: A mixture of 2,4,6-trimethylbenzophenone and 4-methylbenzophenone, manufactured by IGM Resins Co., Ltd., product name: ESACURE TZT

[0056] (D) Component ·Particle 1: Average particle diameter (D 50 ) 5.5μm, ZrO2 calcium aluminosilicate hydrate, manufactured by Mizusawa Chemical Industries, Ltd., product name: Shilton JC-50 ·Particle 2: Average particle diameter (D 50 ) 3.1μm, ZrO2 calcium aluminosilicate hydrate, manufactured by Mizusawa Chemical Industries, Ltd., product name: Shilton JC-30 ·Particle 3: Average particle diameter (D 50 ) 3.1μm, urethane resin, manufactured by Negami Chemical Industries, Ltd., product name: ART PEARL CE-1000T ·Particle 4: Average particle diameter (D 50 )6.5μm, urethane resin, manufactured by Negami Kogyo Co., Ltd., product name: ART PEARL C-800T ·Particle 5: Average particle diameter (D 50 )11.1μm, urethane resin, manufactured by Negami Kogyo Co., Ltd., product name: ART PEARL C-600T ·Particle 6: Average particle diameter (D50 )22.7μm, urethane resin, manufactured by Negami Kogyo Co., Ltd., product name: ART PEARL C-300T ·Particle 7: Average particle diameter (D 50 ) 10.5μm, (meth)acrylic resin, AICA Corporation Ganzpearl GM-1001 ·Particle 8: Average particle diameter (D 50 ) 11.5 μm, amorphous silica, manufactured by PQ Corporation, product name: GASIL HP710 Average particle size of particles 1 to 8 (D 50 The average particle diameter (D) was measured using a laser diffraction / scattering particle size distribution analyzer, Microtrac MT3000II (Microtrac Bell). IPA was used as the circulating solvent, and the particles were thoroughly dispersed by ultrasonic waves for 3 minutes before the measurement. 50 ) was obtained.

[0057] [Example 1] <Production of Coating Composition> A coating composition was produced according to the formulation shown in Table 1. Specifically, components (B) and (C) were added to a metal container and stirred with a disperser until completely dissolved. Then, component (A) was further added and mixed and stirred until homogenous. Next, component (D) was added and stirred for 30 minutes to obtain a coating composition.

[0058] [Examples 2 to 25, Comparative Examples 1 to 27] Coating compositions were obtained in the same manner as in Example 1, except that the components were changed to the proportions shown in Tables 2 to 9.

[0059] <Measurement of the average particle size of the coating composition> The average particle diameter (D 20 , D 50 , D 70 The measurement results are shown in Tables 1 to 9.

[0060] [Table 1]

[0061] [Table 2]

[0062] [Table 3]

[0063] [Table 4]

[0064] [Table 5]

[0065] [Table 6]

[0066] [Table 7]

[0067] [Table 8]

[0068] [Table 9]

[0069] Weight average molecular weight (Mw, Mw mix ) and number average molecular weight (Mn) Weight average molecular weight (Mw, Mw mixThe weight average molecular weight (Mw, Mw) and number average molecular weight (Mn) were measured using a gel permeation chromatography (GPC) "HLC-8320GPC" (Tosoh Corporation). The column used was a TSKgel SuperHZM-N* TSKgel SuperHZ2000 x 2 (Tosoh Corporation). A calibration curve was also prepared using EasiCal PS-2 (Agilent Corporation) as the standard polystyrene. The measurements were performed at a column oven temperature of 40°C using 10 μL of a solution in which the urethane (meth)acrylate oligomer was dissolved in tetrahydrofuran to a concentration of 0.4% by mass. The weight average molecular weight (Mw, Mw) of the urethane (meth)acrylate oligomer was mix The molecular weight (Mn) and number average molecular weight (M) were calculated using standard polystyrene equivalents. The measurement results are shown in Tables 10 to 18.

[0070] Calculation method for weight average molecular weight (Mw / F) per functional group of a single urethane (meth)acrylate oligomer when one type of urethane (meth)acrylate oligomer is used: Weight average molecular weight per functional group of urethane (meth)acrylate oligomer (Mw / F) = Weight average molecular weight of urethane (meth)acrylate oligomer (Mw) / Number of functional groups of urethane (meth)acrylate oligomer (F)

[0071] When multiple types of urethane (meth)acrylate oligomers are used, the weight average molecular weight (Mw mix / F mix ) is calculated as follows: When n types of urethane (meth)acrylate oligomers were mixed, the mixed urethane (meth)acrylate oligomers were assumed to be one urethane (meth)acrylate oligomer, and the number of functional groups was calculated using the following formula. Number of functional groups of mixed urethane (meth)acrylate oligomer (F mix)={(mass (g) of urethane (meth)acrylate oligomer 1 / number average molecular weight Mn of urethane (meth)acrylate oligomer 1×number of functional groups of urethane (meth)acrylate oligomer 1)+(mass (g) of urethane (meth)acrylate oligomer 2 / number average molecular weight Mn of urethane (meth)acrylate oligomer 2×number of functional groups of urethane (meth)acrylate oligomer 2) +··· + (mass (g) of urethane (meth)acrylate oligomer n / number average molecular weight Mn of urethane (meth)acrylate oligomer n × number of functional groups of urethane (meth)acrylate oligomer n)} / {(mass (g) of urethane (meth)acrylate oligomer 1 / number average molecular weight Mn of urethane (meth)acrylate oligomer 1) + (mass (g) of urethane (meth)acrylate oligomer 2 / number average molecular weight Mn of urethane (meth)acrylate oligomer 2) +··· + (mass (g) of urethane (meth)acrylate oligomer n / number average molecular weight Mn of urethane (meth)acrylate oligomer n)} The weight average molecular weight (Mw) per functional group of a urethane (meth)acrylate oligomer that is a mixture of multiple types of urethane (meth)acrylate oligomers. mix / F mix ) = Weight average molecular weight (Mw) of a urethane (meth)acrylate oligomer obtained by mixing multiple types of urethane (meth)acrylate oligomers mix ) / Functional group number of mixed urethane (meth)acrylate oligomer (F mix )

[0072] <Production of substrate with cured coating film> In Examples 1 to 21 and Comparative Examples 1 to 22, China plywood was used as the substrate, and in Examples 22 to 25 and Comparative Examples 23 to 27, maple decorative plywood was used. The following procedures (1) to (7) for typical wooden flooring UV coating were carried out to produce substrates with a cured coating film having a total thickness of about 80 μm. In the following procedure (7), the coating film made of the paint composition had a thickness of about 11 μm. A roll coater was used as the coating machine. (1) The substrate was polished with #400 abrasive paper. (2) On the polished substrate, apply about 2.0 g / shaku of ultraviolet curing paint (manufactured by Chugoku Paint Co., Ltd., product name: Aurex No. 875F). 2 Apply and irradiate with 100mJ / cm2 high pressure mercury lamp 2 The mixture was cured with. (3) UV-curable paint (manufactured by Chugoku Paint Co., Ltd., product name: Aurex No. 821F LV) approx. 1.2 g / shaku 2 High pressure mercury 100mJ / cm 2 The mixture was cured with. (4) Apply UV-curable paint (manufactured by Chugoku Paint Co., Ltd., product name: Aurex No. 663B HV) at approximately 1.5 g / shaku. 2 Then, apply UV-curable paint (manufactured by Chugoku Paint Co., Ltd., product name: Aurex No. 663B-3) at a rate of about 1.5 g / shaku. 2 High pressure mercury 100mJ / cm 2 The mixture was cured with. (5) Intermediate polishing was performed using #400 abrasive paper. (6) Apply UV-curable paint (manufactured by Chugoku Paint Co., Ltd., product name: Aurex No. 859SN-EX) at approximately 1.0 g / shaku. 2 High pressure mercury 100mJ / cm 2 The mixture was cured with. (7) The coating composition prepared above is applied in an amount of about 1.1 g / shaku. 2 Apply the solution and apply it under an excimer UV lamp (Ushio Electric Co., Ltd., 40 mJ / cm 2 , oxygen concentration 1000 ppm), then a high-pressure mercury lamp (I-Graphics, 400 mJ / cm 2 ) and hardened.

[0073] <Evaluation of substrates with cured coating> <Glossiness> A gloss meter (micro-TRI-gloss [manufactured by BYK-Gardner]) was used to measure the 60° gloss and 85° gloss of the cured coating surface of the resulting substrate with the cured coating. The 60° gloss and 85° gloss were measured by receiving light incident on the cured coating surface at an angle of 60° or 85° from the perpendicular direction at an angle of 60° or 85° from the perpendicular direction at the cured coating surface. The cured coating was evaluated according to the following evaluation criteria to determine whether it was low gloss. The measurement results are shown in Tables 10 to 18. (Evaluation Criteria) ◯: Both the 60° gloss and the 85° gloss are 5.0 or less. ×: At least one of the 60° gloss and the 85° gloss exceeds 5.0.

[0074] <Appearance evaluation> The coating surface of the substrate with the cured coating was visually inspected for uneven gloss and evaluated according to the following criteria. The measurement results are shown in Tables 10 to 18. (Evaluation Criteria) ◯: There was absolutely no unevenness in gloss. Δ: There was some unevenness in gloss, but this did not cause any problems in practical use. ×: There was uneven gloss.

[0075] <Contamination resistance test 1> The coating surface of the substrate with the cured coating was covered with a polypropylene cap (inner diameter 23 mm) filled with commercially available blue office ink, and placed horizontally with the coated surface facing up. After leaving it for 1 hour, it was washed with water using a cloth. After rinsing, the marks were visually observed and evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 10 to 18. (Evaluation Criteria) A: There was no trace at all. △: There was a slight mark, but it did not affect practical use. ×: Dark marks were present.

[0076] <Contamination resistance test 2> The test was conducted in accordance with the Japanese Agricultural Standards (JAS) Contamination A test for plywood. The substrate with the cured coating was placed horizontally, and then a 10 mm wide line was drawn on the coating surface of the substrate with the cured coating using commercially available office blue ink, oil-based ink (black) (specified in JIS S 6037 (marking pen)), and red crayon (specified in JIS S 6026 (crayon and pastel) or an ink with equivalent performance), and left for 4 hours, after which the line was wiped off with a cloth soaked in a solvent or detergent. After wiping, the marks were visually observed and evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 10 to 18. (Evaluation Criteria) A: There was no trace at all. △: There was a slight mark, but it did not affect practical use. ×: Dark marks were present.

[0077] <Chemical resistance test> The tests were conducted in accordance with the acid resistance, alkali resistance, and thinner resistance tests stipulated by the Japanese Agricultural Standards (JAS) for plywood. Acid resistance test The substrate with the cured coating is placed horizontally, and then a 5% aqueous solution of acetic acid is dropped onto the coating surface of the substrate with the cured coating. The substrate is covered with a watch glass for 6 hours, and then immediately washed with water and left indoors for 24 hours. Alkali resistance test The substrate with the cured coating is placed horizontally, and then a 1% aqueous solution of sodium carbonate is dropped onto the coating surface of the substrate with the cured coating. The substrate is covered with a watch glass for 6 hours, and then immediately washed with water and left indoors for 24 hours. -Thinner resistance test The substrate with the cured coating is placed horizontally, and lacquer thinner is dropped onto the coating surface of the substrate with the cured coating. The substrate is covered with a watch glass for 6 hours, and then left indoors for 24 hours. After each test, the appearance was visually inspected and evaluated according to the following criteria. The evaluation results are shown in Tables 10 to 18. (Evaluation Criteria) ○: There was no change in appearance before and after the test. △: There was a change in gloss before and after the test. ×: There was a significant change in gloss or discoloration before and after the test.

[0078] <Rubbing resistance test> The substrate with the cured coating was placed horizontally, and then the coating surface of the substrate with the cured coating was rubbed back and forth 30 times with a 7 cm x 4 cm piece of steel wool #0000 (product name: Bonstar) under a load of 2 kg. After cleaning the surface after the test with a paper rag or the like, the 60° gloss and 85° gloss were measured. The change in gloss was evaluated according to the following evaluation criteria. The gloss measurement method was as described above. The evaluation results are shown in Tables 10 to 18. (Evaluation Criteria) ◯: The change in gloss before and after the test in both 60° gloss and 85° gloss was less than 5.0. ×: The change in at least one of the 60° gloss and 85° gloss before and after the test was 5.0 or more.

[0079] <Surface shape measurement> The arithmetic mean curvature Spc of the peaks and the developed area ratio Sdr of the interface of the surface roughness parameters (ISO25178 compliant) of the coating surface of the cured coating substrate were measured for a rectangle (496 μm × 374 μm) at any point on the surface shape of the coating surface of the cured coating substrate using a shape analysis laser microscope (VK-X1000 (controller unit) / VK-X1050 (measurement unit), Keyence Corporation) with an objective lens of 50x, laser wavelength of 661 nm, and measurement mode: shape measurement / laser confocal. The measurement results are shown in Tables 10 to 18.

[0080] <Measurement of the average particle size of particles (D) in the cured coating film> The average particle diameter of particles (D) in the cured coating film was measured using a scanning electron microscope (SEM) with an energy dispersive X-ray analyzer (EDX) ("S-3400N", Hitachi High-Tech Corporation), or a laser microscope for shape analysis ("VK-X1000 (controller unit) / VK-X1050 (measurement unit)", Keyence Corporation) in a manner similar to the method (a) and (b). The longest diameter of the particle was taken as the particle diameter, regardless of the shape of the particle (D), and 40 particles were measured at random, and the average value of these particle diameters was calculated. The average particle diameter values ​​are shown in Tables 10 to 18. In the tables, "a+b" is the average value of the measurement results obtained by both measurement methods.

[0081] [Table 10]

[0082]

Table 11

[0083]

Table 12

[0084]

Table 13

[0085]

Table 14

[0086]

Table 15

[0087]

Table 16

[0088]

Table 17

[0089]

Table 18

Claims

1. A coating composition comprising a urethane (meth)acrylate (A), a (meth)acrylate monomer (B), a photopolymerization initiator (C) and particles (D), The weight average molecular weight (Mw / F) per functional group of the urethane (meth)acrylate (A) is 1,500 or more, The average particle diameter (D 50 ) is 5.0 μm or more.

2. The coating composition according to claim 1, wherein the urethane (meth)acrylate (A) has a functionality of 3 or more.

3. The coating composition according to claim 1 , wherein the particles (D) comprise organic particles.

4. The coating composition according to claim 3 , wherein the organic particles are urethane resin particles.

5. The average particle diameter (D 50 2. The coating composition according to claim 1, wherein the average particle size is 8.0 μm or more.

6. The coating composition according to claim 1, wherein the content of the particles (D) is 5.0 mass% or more relative to 100 mass% of the solid content of the coating composition.

7. The coating composition according to any one of claims 1 to 6, which is for excimer UV curing.

8. A cured coating film formed from a coating composition containing a urethane (meth)acrylate (A), a (meth)acrylate monomer (B), a photopolymerization initiator (C) and particles (D), the developed area ratio Sdr of the interface on one surface of the cured coating film is 0.300 or more, and the arithmetic mean curve Spc of the peaks is 3,000 or more; The average particle size of the particles (D) in the cured coating film is 3.2 μm or more.

9. A step of applying a coating composition containing a urethane (meth)acrylate (A), a (meth)acrylate monomer (B), a photopolymerization initiator (C) and particles (D) onto a substrate; a step of irradiating the coated surface of the substrate with excimer UV light to form a cured coating film having an interface developed area ratio Sdr of 0.300 or more, an arithmetic mean curve Spc of the peaks of 3,000 or more, and an average particle size of particles (D) in the cured coating film of 3.2 μm or more; A method for producing a cured coating film comprising the steps of:

Citation Information

Patent Citations

  • Exclusive items

    JP2022061031A

  • Decorative sheet

    WO2022181354A1

Cited By

  • Active energy ray-curable coating composition for flooring, cured coating film, and substrate with cured coating film

    JP7802997B1

  • Uv-curable high-hardness Anti-scratch coating composition and method for preparing the same

    KR102982121B1